2004
DOI: 10.1073/pnas.0308679101
|View full text |Cite
|
Sign up to set email alerts
|

Venezuelan kindreds reveal that genetic and environmental factors modulate Huntington's disease age of onset

Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disease caused by a triplet (CAG) expansion mutation. The length of the triplet repeat is the most important factor in determining age of onset of HD, although substantial variability remains after controlling for repeat length. The Venezuelan HD kindreds encompass 18,149 individuals spanning 10 generations, 15,409 of whom are living. Of the 4,384 immortalized lymphocyte lines collected, 3,989 DNAs were genotyped for their HD alleles, represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
214
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(223 citation statements)
references
References 25 publications
6
214
1
2
Order By: Relevance
“…The number of CAG repeats in normal chromosomes is significantly higher in populations presenting high prevalence of HD Squitieri et al, 1994). Higher averages of CAG numbers in normal chromosomes were found in Mexico, Cuba, Brazil, Europe, North America, and Oceania (Raskin et al, 2000;Wexler et al, 2004;McNicoll et al, 2008;Alonso et al, 2009;Semaka et al, 2013b;Vázquez-Mojena et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
“…The number of CAG repeats in normal chromosomes is significantly higher in populations presenting high prevalence of HD Squitieri et al, 1994). Higher averages of CAG numbers in normal chromosomes were found in Mexico, Cuba, Brazil, Europe, North America, and Oceania (Raskin et al, 2000;Wexler et al, 2004;McNicoll et al, 2008;Alonso et al, 2009;Semaka et al, 2013b;Vázquez-Mojena et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
“…Classically, age at onset was established on the basis of 'score equal to 4', according to the DCL of the United Huntington' s Disease Rating Scale (UHDRS) in a mutation carrier subject 19 . Nevertheless, several reports on pre-manifest subjects remarked the occurrence of non-motor behavioral and cognitive manifestations anticipating the typical motor signs and symptoms by even many years 19,20,21,22,23 , thus making the definition of age at onset in JHD still controversial 5,6,19,20,21,22,23 . Recently, Reilmann et al, suggested to take in account the whole individual medical history, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we believe that this series may contribute to the expansion of knowledge of the JHD variant, which is already rare and, particularly so, due to the limited number of reports focusing on this topic from South America, with the exception of the Venezuelan community 23 .…”
mentioning
confidence: 99%
“…The expansion length is variable and explains much of the heterogeneity in the age at which mutation‐carriers receive a clinical diagnosis of manifest disease (Duyao et al, 1993). A large portion of variability in age at onset, however, remains unexplained by the gene‐mutation and is likely the result of other factors, both genetic and environmental (Wexler et al, 2004). Identifying these factors and their associated biological processes could provide additional targets for therapeutic interventions that may modify disease progression.…”
Section: Introductionmentioning
confidence: 99%